Makerspaces: A Practical Guide for Librarians - Miller, Karen (2015)
Book review: Makerspaces: A Practical Guide for Librarians, by John J. Burke, Lanham, MD., Rowman & Littlefield, 2014, ISBN 978-1-4422- 2967-9 (paperback).